Artistic Image of Hetman Ivan Masepa through the prism of synthesis of arts of the Ukrainian diaspora - Karas, Hanna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
Relevance of the study. The figure of Hetman Ivan Mazepa as a state-maker has remained relevant to the creation of artistic images in various forms of art during the last three centuries. It remains significant for Ukraine today, when our country defends its right to a European choice — the choice of freedom. The artistic aspect of the Hetman in synthesis of words and music of the Ukrainian diaspora artists in the twentieth century remains insufficiently studied aspect. Main objective(s) of the study is to analyze the image of Hetman Ivan Mazepa through the prism of synthesis of arts of the Ukrainian diaspora — literature and music. Methodology. To achieve this goal, the following scientific approaches were used: historiographic (for studying historical research on this issue), bibliographic (for compiling a list of sources and books, their scientific description), analytical (for the theoretical analysis of the musical form of compositions), comparative (for the comparative analysis of poetic and musical texts and to observe interrelation of these two art forms). The achievement of the goal determines the following tasks: to identify and analyze the literary and musical works of the Ukrainian diaspora, which created a bright artistic image of Ivan Mazepa. The main results and conclusions. The author considered features of the creation of the artistic image of the Ukrainian Hetman Ivan Mazepa through the prism of synthesis of arts of the Ukrainian diaspora (literature, music, performance). For this purpose, the author analyzed the musical works of composers Mykola Fomenko and Serhii Yaremenko on the texts of Yar Slavutych. It is revealed that Mazepa’s artistic image in the system of synthesis of arts of the Ukrainian diaspora (poem, cantata) as a phenomenon of interaction between word and music has a patriotic illumination of the Hetman as a state-maker. The interpretations of this image in the interaction of word and music in the historical, ideological, national, aesthetic planes do not contrast among themselves, as the authors of music and poetic texts were Ukrainians, sharing mutual political views and aesthetic positions in arts. This active interaction creates a composition that is an important instrument of revealing the ideological and emotional content of the analyzed works. The literary text encourages the composer to create musical intonations and rhythms that are in harmony with the meaning of words and verbal constructions.